Ghana's tomato market - Ministry of Food and Agriculture, Ghana; International Food Policy Research Institute; Amewu, Sena; Arhin, Eunice; Danso, Jane; Doughan, Roland Ato; Nafrah, Christiana; Owusu, Ivy; Pauw, Karl (International Food Policy Research Institute, 2020)
Tomatoes are a key component in the diets of Ghanaian households. Approximately 440,000 tons of tomato are consumed annually, equivalent to 40 percent of household vegetable expenditure (Van Asselt et al. 2018). Despite government support for the sector, national production has not increased much in the last decade, resulting in domestic supply falling far short of demand. While UN Comtrade (2019) trade statistics for 2007 to 2017 indicate that the country imported only around 8,000 tons of tomato annually, mainly from neighboring Burkina Faso, Van Asselt et al. (2018) put this figure at closer to 100,000 tons or one-quarter of domestic supply. Evidently, large quantities of tomato enter the country informally, making it difficult to estimate actual supply and demand patterns and devise appropriate marketing policies. The perishability of tomato is a major challenge and imparts significant risk on producers and traders. As such, post-harvest handling, transport, storage, and processing losses have been estimated at between 20 and 65 percent of production (Vowotor et al. 2012).